Pengaruh Persepsi Kemudahan Penggunaan, Persepsi Risiko, Persepsi Kepercayaan Pada Generasi Millenials Dalam Menggunakan Mobile Banking: Studi Kasus Pada Nasabah Bank BCA - Subowo, Hery; Noviantika, Tria Adella; Sumantri, Samuel (LPPM IBI Kesatuan, 2023)
This study aims to determine whether Perception of Ease of Use, Perception of Risk, and Perception of Trust have an effect on Mobile Banking Users. The population used in this study is Bank BCA customers throughout Indonesia who use mobile banking. The sample in this study was 160 respondents and the technique used was probability sampling. The data obtained were then processed with SPSS version 26.0. The data analysis method used is quantitative analysis. This analysis includes validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination analysis, t test and f test. Based on the results of the t test, the variable Perception of Ease of Use (X1), the variable Perception of Risk (X2), and the variable Perception of Trust (X3) have a significant influence on Mobile Banking Users (Y). Based on the f test, it is known that the variables of Perception of Ease of Use (X1), Perception of Risk (X2), and Perception of Trust simultaneously have a significant effect on Mobile Banking Users (Y). Keywords: Perception of Ease of Use, Perception of Risk, Perception of Trust, Mobile Banking Users.